2008
DOI: 10.1097/tp.0b013e318189049a
|View full text |Cite
|
Sign up to set email alerts
|

Sirolimus As Primary Immunosuppressant Reduces Left Ventricular Mass and Improves Diastolic Function of the Cardiac Allograft

Abstract: Withdrawal of CNI and replacement with SRL in cardiac transplant recipients results in a decrease in LV mass and improvement in diastolic function. SRL may be useful to attenuate LVH and improve cardiac allograft diastolic function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 45 publications
0
26
1
Order By: Relevance
“…In various other hypertrophy models as well as humans, rapamycin attenuates HCM (27,32,38). However, rapamycin has negative inotropic effects in our study as well as in other models (28).…”
Section: Discussioncontrasting
confidence: 45%
“…In various other hypertrophy models as well as humans, rapamycin attenuates HCM (27,32,38). However, rapamycin has negative inotropic effects in our study as well as in other models (28).…”
Section: Discussioncontrasting
confidence: 45%
“…[7]. Also, studies have shown that rapa served as immunosuppressive drugs in both experimental models and clinical transplantation [21][22][23], but their combined effects on graft survival have not been investigated previously, which forms the focus of this study. Here we reported that CCR5 blockade in combination with rapa prevent both acute and chronic rejection in a fully MHC-mismatched murine model up to 90 days.…”
Section: Discussionmentioning
confidence: 99%
“…Stallone, et al showed that SRI introduction along with CNI withdrawal improved graft survival and reduced interstitial/vascular α-smooth muscle actin expression, slowing down the progression of allograft injury in renal transplant recipients. 32) Kushwaha, et al showed in HTx recipients that conversion from CNI to SRL decreased LVMI along with increased 14) Little has been reported about the anti-proliferative effect of EVL except for several studies in renal transplant recipients. Paoletti, et al showed in a randomized controlled study that EVL therapy along with reduced CyA was effective in the reduction of LVM among renal transplant recipients, mainly due to reduced LV wall thickness, 34) which was consistent with our results.…”
Section: )mentioning
confidence: 99%
“…[8][9][10][11][12] Clinical studies also showed that SRL had an advantage in the improvement of LVH compared with conventional calcineurin inhibitors (CNI) when used as an immunosuppressant in heart or kidney transplant recipients. [13][14][15] However, little is known about how the next generation mTOR inhibitor derivative everolimus (EVL) affects LVM. 13,16,17) EVL has become thus far a major mTOR inhibitor for immunosuppression therapy because of its superiority in terms of fewer adverse effects compared to SRL.…”
Section: Eft Ventricular Hypertrophy (Lvh) Is Observed In Pa-mentioning
confidence: 99%